McGraw-Hill concise encyclopedia of chemistry. (New York : McGraw-Hill, 2004)
Alphabetically arranged entries provide a comprehensive overview of the field of chemistry, offering information on key figures, theories, discoveries, advances, terms, and concepts.
Equivalents of commonly used units for the U.S. customary system and the metric system -- Conversion factors for the U.S. customary system, metric system, and international system -- Defining fixed points of the international temperature scale of 1990 (ITS-90) -- Primary thermometry methods -- Principal spectral regions and fields of spectroscopy -- Recommended values (2002) of selected fundamental constants -- Electromagnetic spectrum -- Standard atomic weights -- Biographical listing.
Includes indexes.
Includes bibliographical references.
Keywords: Chemistry -- Encyclopedias; Chemistry -- Encyclopedias -- English; Chemie; Chemistry -- Encyclopedias; 2